Effective removal of colistin methanesulphonate and formed colistin during intermittent haemodialysis in a patient infected by polymyxin-only-susceptible Pseudomonas aeruginosa. (April 2014) - Luque, Sonia; Sorli, Luisa; Li, Jian; Collado, Silvia; Barbosa, Francesc; Berenguer, Nuria; Horcajada, Juan Pablo; Grau, Santiago
<x content-type="archive" xml:space="preserve">Abstract</x> Colistin use has reemerged for the treatment of infections caused by multidrug-resistant Gram-negative bacteria. However, the information on its pharmacokinetics is limited, especially in patients with end-stage renal disease, in which dosage adjustments are contradictory, and evidences the need to investigate the removal of colistin through renal replacement therapies like haemodialysis. This case study showed efficient removal of colistin methanesulphonate and formed colistin during intermittent haemodialysis in a patient infected by polymyxin-only-susceptible Pseudomonas aeruginosa. These results suggest the importance to monitor colistin plasma concentrations in these patients to minimize treatment failure due to suboptimal exposure to antibacterial colistin.